KESULITAN DIAGNOSIS DAN TERAPI PADA LIMFOMA PANKREAS DISERTAI SINDROMA KAUDA EQUINA - Ridwan, Muhammad; Dharmayuda, Tjokorda Gde (journal of internal medicine, 2012)
Lymphoma, part of non-Hodgkin’s lymphoma, is a rare malignancy in pancreas. Its clinical presentations and supporting laboratory and imaging results are similar to those of pancreas adenocarcinoma. Apart from pancreas, extranodal type of non-Hodgkin can involve many other organs including bone marrows, nervous system, and kidneys. Treatment should be focused on emergency priority and the underlying cause. In this case report, we have documented a 44 year-old man who initially presented jaundice and abdominal mass and then diagnosed with pancreas tumor. However, pathology anatomy and histochemistry examinations of peripancreas tissue biopsy and indicated a non-hodgkin lymphoma of pancreas, in form of diffuse large B cell lymphoma, intermediate grade. The patient was developing cauda equina syndrome a week after laparotomy. Discussion among team suggested that both conditions may have the same root: lymphoma. The patient was then put on CHOP regiments of chemotherapy program and later, also underwent a spinal decompression procedure. Overall, jaundice, abdominal mass and other related symptoms subsided, and quality of life improved, although some cauda equina symptoms remained.
Keywords: pancreas lymphoma, cauda equina syndrome